The human hippocampus can pattern separate memories by meaning - Alex Ilyés; Borbála Mónika Brosig; György Mező; Attila Keresztes (Proceedings of the National Academy of Sciences, 2026)
Hippocampal pattern separation is a neural operation supporting mnemonic discrimination of highly similar memories by orthogonalizing neural inputs into nonoverlapping representations. In humans, pattern separation is thought to support the specificity of episodic memories. Recent neuroimaging studies suggest that the hippocampus can also access and manipulate semantic information. However, it is unclear whether the hippocampus can pattern separate highly similar semantic representations. Here, we tested multiple neural and behavioral signatures of pattern separation using high-resolution functional MRI during a well-established memory discrimination task where we manipulated semantic similarity in a multidimensional conceptual space using word-embeddings. Thirty young adults (Mage = 21.1, 16 females) saw adjective-noun phrases (e.g., “exotic zoo”) that were later repeated exactly as before or modified with semantically similar adjectives (e.g., “strange zoo”). Crucially, we presented exact and modified repeats both during an incidental encoding and a two-choice recognition phase, where mnemonic discrimination was assessed. Consistent with pattern separation, we found attenuated repetition suppression for modified repeats in repetition sensitive clusters of the hippocampal head, which was evident at both high and low levels of similarity with no difference between two a priori defined similarity bins. In addition, within participants, the neural signature of pattern separation was associated with mnemonic discrimination at recognition. Finally, clusters sensitive to repetitions during encoding differentiated lures from foils at recognition. These results suggest that hippocampal pattern separation is triggered by fine-grained differences in meaning and supports the creation of highly specific representations of memories overlapping in semantic memory.